Modeling Factors Influencing Passenger Decisions on Intercity and Regional Railway Train - Leinia, Audinda Virsa; Sidhiq, Sham (Kadiri University, 2025)
The dependence on private vehicles has grown significantly in the past decade, impacting travel experience quality. Transportation companies need to focus on enhancing the loyalty through exploring choice behavior. Existing research often focuses on typical service attributes, but the comparative impact with more complex variables factors remains underexplored. This study aims to identify factors influencing intercity and regional rail passenger travel decisions. This research explores sociodemographics, travel behavior, and factors affecting their mode of choice. Survey data using questionnaires were collected from 649 respondents across four intercity and five regional rail services. Logistic regression models were developed with variable selection validated using the Wald significance test and model evaluation conducted. The results indicate that intercity rail travel choices are significantly influenced by disposable income, trip purpose, and onboard comfort attributes such as air conditioning and cleanliness. In contrast, regional train choice is largely driven by factors such as occupancy rate, frequency of use, travel time reduction, and cost sensitivity. These findings confirm that intercity and regional passengers represent distinct market segments shaped by different behavioral priorities. The resulting models demonstrated strong performance, with the intercity model explaining 76.8% of the variance in choice and achieving a predictive accuracy of 82.1%, while the regional model explained 58.9% of the variance with an accuracy of 63.8%. The findings suggest that fare adjustment strategies and service development focused on air conditioning, cleanliness, and travel time can enhance ridership for both train types, thereby enhancing the overall attractiveness of the public transportation system.